Unusual case of acute coronary syndrome: inferior wall myocardial infarction 19 years young male presented with fever and right ankle cellulites treated with tissue plasminogen activator and its out come - Patel, Dipesh Sureshbhai; Das, V. K.; Desai, Keyur (International Journal of Basic & Clinical Pharmacology, 2017)
Unusual case of acute coronary syndrome: inferior wall myocardial infarction in 19yrs young male patient presented with fever and right ankle cellulites with fungal infection, thrombolysis was done with injection tenectaplase a newer tissue plasminogen activator with Troponin-T positive. Tenectaplase drug showed ECG changes within 30 minutes of thrombolysis with normal coronary during the angiography and preserved the left ventricular ejection function making it a successful thrombolysis by the tissue plasminogen activator (TPA) in young patient with myocardial infarction.